Demonstration-Based Poetry Writing Pedagogy to Strengthen Education for Sustainable Development (ESD) in Fostering a Culture of National Resilience: A Classroom Action Research Study - Marsudi, Martinus; Saputra, Ardi (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2026)
Education in the 21st century requires integrating sustainability values to support the global agenda of Education for Sustainable Development (ESD). Literary education, particularly poetry writing, has strategic potential to foster cultural awareness, social sensitivity, and reflective thinking as foundations of national resilience culture. This study analyzes how demonstration-based poetry writing pedagogy strengthens ESD implementation through students’ cultural and social competencies. Using a Classroom Action Research design with three cycles, the study involved 29 eighth-grade students at a junior high school in Sidoarjo, Indonesia. Data were collected through observation, poetry writing assessments, and documentation, then analyzed descriptively using quantitative and qualitative approaches. The findings show significant improvement in students’ writing competence and participation, with learning mastery increasing from 44.82% in Cycle I to 100% in Cycles II and III. Demonstration-based pedagogy also promoted cultural value internalization, self-confidence, social awareness, character formation, cultural identity, and social resilience aligned with ESD principles.